Analysis and design of control systems using MATLAB - Dukkipati, Rao V. (New Age International (P) Ltd. Publishers, 2006)
Control systems engineering is a multidisciplinary subject and presents a control engineering methodology based on mathematical fundamentals, and stresses physical system modeling. Analysis and design of control systems using MATLAB book is designed as an introductory undergraduate course in control systems for engineering students of all disciplines. The classical methods of control systems engineering are covered here using MATLAB software: matrix analysis, Laplace transforms and transfer functions, root locus analysis and design, frequency response methods of analysis including Bode, Nyq.